Awareness of Dengue Disease among Female Community Health Volunteers of Sainamina Municipality, Nepal - Lamsal, Sunita (SNPRC Journal, 2023)
Dengue is a mosquito-borne viral infection that is a major public health problem in Nepal. Female community health volunteers play a vital role in dengue prevention and control by providing health education and services to the community. This study aimed to provide a comprehensive understanding of the level of dengue awareness among female community health volunteers in Sainamina Municipality, Nepal. This study involved a cross-sectional survey of 50 female community health volunteers aged 20 and above, actively engaged in health-related activities in Sainamina Municipality. A structured questionnaire was used to gather information on their knowledge of dengue transmission, symptoms, preventive measures, and available treatments. The findings revealed that 98 percentage of the female community health volunteers had a general knowledge of dengue, but there was some confusion regarding the specific mode of transmission. Their knowledge about the signs and symptoms, transmission routes, and preventive measures was inadequate. Only 74 percentage identified that dengue is transmitted through the bite of an infected Aedes mosquito. Additionally, 48 percentage of respondents were able to identify the Aedes mosquito, and 36 percentage knew that there was no specific medicine for dengue patients. Targeted efforts are needed to address the areas of confusion among the female community health volunteers and enhance awareness of comprehensive prevention strategies. It is recommended to conduct training, provide educational materials, and encourage them to share their knowledge with their communities to improve dengue awareness and prevention efforts.